“Prevalencia de patologías orales en pacientes VIH positivo mediante revisión bibliográfica en el periodo octubre 2023-febrero 2024” - Carrión Reyes, Nataly Nicole (2024)
The World Health Organization (WHO) reports that HIV infection affects the immune system by attacking white blood cells, weakening the immune defenses and increasing susceptibility to opportunistic diseases. Among these are oral diseases, which are often the earliest indicators of HIV in people and reflect the progressive deterioration of the immune system. Although many of these conditions may not appear until the advanced stages of the disease, they can still have a significant impact on the health of patients. Therefore, the aim of this research project is to review the most common oral pathologies in HIV- positive patients and to investigate the factors that contribute to the development of these conditions. A total of 30 scientific articles were included in this descriptive, analytical, bibliographic, and cross-sectional study, all of which satisfy the pre-specified inclusion criteria and were obtained from various databases. Additionally, the study shows that 60 percent of the authors identify the CD4+ cell count as a critical factor in the weakening of the immune system, which contributes to the development of oral lesions. Regarding prevalence, oral candidiasis is the most common condition, affecting 66.66 percent of cases, followed by hairy leukoplakia, with a prevalence of 53.33 percent. This study provides a comprehensive framework for understanding oral pathologies in HIV-positive patients, improving awareness of both risk factors and the prevalence of these conditions. Moreover, thisinsight enables earlier diagnosis. The findings could play a key role in shaping prevention and care strategies within the field of oral health for people living with HIV